2019
DOI: 10.4274/tjo.galenos.2018.90359
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Body Position on Intraocular Pressure Measured with Rebound Tonometer

Abstract: Objectives:It is important to determine variables that influence intraocular pressure (IOP) measurement. This study aimed to evaluate the effect of body position on IOP.Materials and Methods:The study included 52 right eyes of 52 patients who presented to the ophthalmology department of our hospital and had no ocular disease except refractive errors. IOP was measured with an Icare PRO tonometer while patients were in sitting, standing, and supine positions, with intervals of 10 minutes between the positions. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
8
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
2
8
2
Order By: Relevance
“…It is possible that the influence of body position on the IOP result is lower in elderly people than in young people. This result confirms the findings of Mayali et al, 34 who reported that gender and age do not affect IOP measurements in different body positions (a group of subjects in the age range from 23 to 47 years old). However, there are studies in the literature in which the conclusions are in contrast with ours.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It is possible that the influence of body position on the IOP result is lower in elderly people than in young people. This result confirms the findings of Mayali et al, 34 who reported that gender and age do not affect IOP measurements in different body positions (a group of subjects in the age range from 23 to 47 years old). However, there are studies in the literature in which the conclusions are in contrast with ours.…”
Section: Discussionsupporting
confidence: 92%
“…[17][18][19][20][21][29][30][31][32][33] This phenomenon began to be intensively considered and investigated some time ago due to the large number of bedridden patients requiring IOP measurements. However, the statistical significance of the difference between IOP measured in miscellaneous body positions is controversial, for example, Mayali et al 34 reported that the differences in IOP are not statistically significant in a group of healthy subjects. Other articles have shown that intraocular pressure measured in the supine position is significantly higher than the IOP values in the sitting or standing positions.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found no significant correlation between IOP measurement and age of glaucomatous children, as well as, no significant relation between IOP measurement and gender of glaucomatous children. This goes in line with, Mayal et al 4 who demonstrated that, Gender and age had no bearing on IOP in various body postures.…”
Section: Discussionsupporting
confidence: 89%
“…The eyes' IOP is known to be fluctuate depending on the body position. 12 The IOP measurement with a contact lens sensor (CLS) has solved this problem. The Triggerfish CLS (Sensimed, Lausanne, Switzerland) was developed to continuously monitor habitual IOP fluctuations for a 24-hour period by measuring changes in the eye's circumference in the area of the corneoscleral junction.…”
mentioning
confidence: 99%
“…Most of the investigations of IOP fluctuations have measured the IOP with Goldmann applanation tonometry (GAT) several times a day with the subject in a sitting position; however, such a method is inaccurate and lacks objectivity because it does not take into account the changes in a person’s body position and might not be able to measure the peak IOP. The eyes’ IOP is known to be fluctuate depending on the body position 12…”
mentioning
confidence: 99%